The importance of the operational auditing instilling confidence on the report of the external auditor - benzerrouk, Zakia Seid; Esawi, Khaldah Abdallah Mohammed (Journal of Economic, Administrative and Legal Sciences, 2019)
The basic topic of This research is to evaluate, from the professionals’’ point of view, the effectively of the operational auditing in instilling confidence on the report of the external auditor. It also presents a Field study on a sample drawn from the board of governors of the accounts. To achieve This point, the research depends on the employment of a theoretical model which includes a number of indicators that would be invoked in the Field study. These indicators are linked to the extent of the clarity and comprehensiveness of the approach in supporting the credibility of the report of the external auditor. To achieve thèse objectives, the researchers suggested the following assumptions: -The basic assumption: - The operational auditing participates in supporting the credibility of the external auditor reports. -The minor assumptions: 1-The operational auditing is a modern concept which expanded to include the measurement of the quality and effectiveness and performance évaluation, which Will contribute to establish the credibility of the report of the External Auditor. 2- There is an impact of the operational auditing in reducing the risks to give greater credibility to the report of the External Auditor. The researchers found the following results: 1- The study asserts that the expansion of the operational auditing to include the measurement of the effectively and performance évaluation contribute in instilling credibility on the report of the external auditor. The study also proved, through the practical analysis, that the expansion in this type of auditing contribute and adds credibility on the report of the external auditor and this point asserts the achievement of the first assumption. 2- The study also proved that there is a relationship between the operational auditing and reducing the risks to increase the credibility of the report of the external auditor. This point asserts the achievement of the second assumption. 3-The study also asserted the relationship between the operational auditing and achieving the credibility of the report of the external auditor.